Geological, geophysical and plate kinematic constraints for models of the India-Asia collision and the post-Triassic central Tethys oceans - Parsons, AJ; Hosseini, K; Palin, RM; Sigloch, K (Elsevier, 2020)
In this study, we integrate bedrock datasets, observations of subducted slabs in the mantle, and plate kinematic constraints, to constrain models for the India-Asia collision and the central Tethys oceans. To accomplish this, we review: (1) the post-Triassic bedrock record of subduction in Tibet; (2) seismic tomographic imaging of subducted slabs in the mantle; (3) timing of the India-Asia collision; and (4) the pre-collisional size of Greater India. Following the assumption that slabs sink vertically through the mantle, their positions and geometries determined from seismic tomography constrain the locations and kinematics of paleo-subduction zones. Integrating this with bedrock constraints allows us to constrain post-Triassic subduction zone configurations for the central Tethys oceans. Neotethys was consumed by at least two subduction zones since the Jurassic. At the onset of the India-Asia collision at 59 ± 1 Ma, one subduction zone was active along the southern Asian continental margin at ~20°N. At that time, a second may have been active at subequatorial latitudes, but support for this from a bedrock perspective is lacking. This subduction zone configuration allows for three reconstructions for Greater India: The (1) minimum-area; (2) enlarged-area; and (3) Greater India Basin reconstructions. We integrate these reconstructions and subduction zone configurations in a plate kinematic framework to test their validity for the India-Asia collision. No single model is entirely satisfactory and each invokes assumptions that challenge accepted concepts. These include our understanding of suture zones, and the limits of continental subduction. We explore these challenges and their implications for our understanding of the India-Asia collision and continental collisions in general.